2012
DOI: 10.1159/000340055
|View full text |Cite
|
Sign up to set email alerts
|

Is PCA3 Score Useful in Preoperative Staging of a Single Microfocus of Prostate Cancer Diagnosed at Saturation Biopsy

Abstract: Objective: To evaluate prostate cancer gene 3 (PCA3) score accuracy in preoperative staging of cases of single microfocus of prostate cancer (PCa; less than 5% with Gleason score ≤6) diagnosed after repeat saturation biopsy (median 30 cores). Methods: From January 2009 to March 2012, 38 patients (median 64 years) with a microfocus of PCa, median PSA of 9.1 ng/ml and T1c clinical stage underwent radical retropubic prostatectomy. PCA3 score (cut-off of 20 vs. 35) was evaluated in predicting insignificant PCa (pI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Including the PCA3 score into multivariable models increased the accuracy of CIPCa prediction [ 118 ]. Also, more recent studies confirm this result with high diagnostic accuracy (equal to 86.8%) of PCA3 score cut-off >20 in the presence of a microfocus of significant prostate cancer [ 126 ]. Contrary to these data, Durand et al suggested that the PCA3 score of >35 represented an independent predictor in a multivariate analysis of a tumor volume >0.5 mL [ 127 ].…”
Section: Markers In the Diagnosis Of Prostate Cancermentioning
confidence: 65%
“…Including the PCA3 score into multivariable models increased the accuracy of CIPCa prediction [ 118 ]. Also, more recent studies confirm this result with high diagnostic accuracy (equal to 86.8%) of PCA3 score cut-off >20 in the presence of a microfocus of significant prostate cancer [ 126 ]. Contrary to these data, Durand et al suggested that the PCA3 score of >35 represented an independent predictor in a multivariate analysis of a tumor volume >0.5 mL [ 127 ].…”
Section: Markers In the Diagnosis Of Prostate Cancermentioning
confidence: 65%
“…This terminology was introduced in 1996; subsequently, EPE was confirmed to be an adverse prognostic factor for PCa (22). Several variables, including the Partin table, MRI, TRUS and digital rectal examination findings, and prostate cancer antigen 3 score, have been studied to assess the predictive power of EPE; however, sensitivities have ranged from only 50-70% (8,9,(23)(24)(25). Thus, there is an urgent need to explore novel and more effective approaches for predicting EPE for determining an appropriate surgical strategy and also for delineating a favourable postoperative adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Various strategies, including Partin nomogram, MRI, prostate cancer gene 3 score, etc., have been studied in an attempt to improve the accuracy of the prediction of ECE [3,21,22,23], but the sensitivity for the detection is still limited to 50-70% [10,14,15]. In 1997, Partin et al [21] established Partin nomograms using tPSA, biopsy Gleason score, and clinical T classification to predict ECE.…”
Section: Discussionmentioning
confidence: 99%